Worker-Firm Screening and the Business Cycle - Jake Bradley (Institute of Labor Economics (IZA), 2022)
There has been a substantial body of work modeling the co-movement of employment, vacancies, and output over the business cycle. This paper builds on this literature, and informed by empirical investigation, models worker and firm search and hiring behavior in a manner consistent with recent micro-evidence. Consistent with empirical findings, for a given vacancy, a firm receives many applicants, and chooses their preferred candidate amongst the set. Similarly, workers in both unemployment and employment, can evaluate many open vacancies simultaneously and choose to which they make an application. Business cycles are propagated through turbulence in the economy. Structural parameters of the model are estimated on U.S. data, targeting aggregate time series. The model can generate large volatility in unemployment, vacancies, and worker flows across jobs and employment state. Further, it provides a theoretical mechanism for the shift in the Beveridge curve after the 2008 recession - a phenomenon often referred to as the jobless recovery. That is, persistently low employment after the recession, despite output per worker and vacancies having returned to pre-crisis levels.
Keywords: J63; J64; 330; Beveridge curve; screening; jobless recovery